The Synergistic Effects of Chitosan-Alginate Nanoparticles Loaded with Doxycycline Antibiotic Against Multidrug Resistant Proteus Mirabilis, Escherichia Coli and Enterococcus Faecalis - Alsaady, Wasan Nabeel; Zaidan, Israa Ali (Iraqi Journal of Science, 2020)
This study focused on the synthesis of chitosan-alginate (CH-ALg) nanoparticles by ionotropic gelation technique using sodium alginate and calcium chloride. The particle size of the synthesized nanoparticles was confirmed by atomic force microscope (AFM) and it was 61.9 nm. While the nature of functional groups present in chitosan nanoparticles was determined by FT-IR analysis. The antibacterial activity of chitosan-alginate was tested against multidrug resistance (MDR) gram- positive (Enterococcus faecalis) and gram-negative (Proteus mirabilis) bacteria. The results showed a significant effect against MDR isolates. The nanoparticles were loaded with the antibiotic doxycycline in order to improve the antibacterial activity and drug delivery efficiency. The synergistic effects of the biosynthesized chitosan-alginate and the loaded doxycycline at different concentrations against MDR bacteria were also investigated. The results showed that doxycycline-loaded nanoparticles have superior effectiveness compared to native doxycycline against gram negative and gram positive bacteria.